A protocol to evaluate the potential of protected areas for birdwatching tourism: a study case in the Brazilian Amazon - Plácido, Ricardo Antônio de Andrade; Borges, Sérgio Henrique; Silva, Edson Guilherme da (Revista Brasileira de Ecoturismo (RBEcotur), 2021)
Birdwatching is a growing segment of ecotourism and South America’s protected areas have an enormous potential to contribute to the development of this activity. We present a simple protocol to assess the potential of protected areas to attract and receive birdwatchers. The protocol is based on the application of raw scores using the following criteria: i) potential of local avifauna to attract birdwatchers, ii) logistic facilities of the protected area, and iii) services for accommodation, communication, health support and transport available in the municipality/ies located near the protected area. The protocol was applied in a protected area located in the State of Acre, in the southwestern part of the Brazilian Amazon. Thirty bird species (11% of avifauna) achieved the highest level of attractiveness for birdwatchers. The protected area and its neighboring municipalities show median capacity for hosting birdwatchers. The application of the protocol in other protected areas will be necessary to improve its applicability. The method, however, could be useful for a preliminary analysis of the birdwatching potential of protected areas.